Factor <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn><mi>t</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn><mrow><mo>(</mo><mi>t</mi><mo>)</mo></mrow><mo>+</mo><mn>4</mn><mrow><mo>(</mo><mn>1</mn><mo>)</mo></mrow></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mfrac><mrow><mn>4</mn><mrow><mo>(</mo><mi>t</mi><mo>+</mo><mn>1</mn><mo>)</mo></mrow></mrow><mrow><mi>t</mi><mo>-</mo><mn>5</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><msup><mrow><mi>t</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>-</mo><mi>t</mi><mo>-</mo><mn>20</mn></mstyle></math> .

Consider the form <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>+</mo><mi>b</mi><mi>x</mi><mo>+</mo><mi>c</mi></mstyle></math> . Find a pair of integers whose product is <math><mstyle displaystyle="true"><mi>c</mi></mstyle></math> and whose sum is <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> . In this case, whose product is <math><mstyle displaystyle="true"><mo>-</mo><mn>20</mn></mstyle></math> and whose sum is <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Write the factored form using these integers.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>t</mi><mo>-</mo><mn>5</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mn>4</mn><mrow><mo>(</mo><mi>t</mi><mo>+</mo><mn>1</mn><mo>)</mo></mrow><mrow><mo>(</mo><mi>t</mi><mo>+</mo><mn>4</mn><mo>)</mo></mrow></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Apply the distributive property.

Apply the distributive property.

Apply the distributive property.

Simplify each term.

Multiply <math><mstyle displaystyle="true"><mi>t</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>t</mi></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><mi>t</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>t</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>t</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>16</mn><mi>t</mi></mstyle></math> and <math><mstyle displaystyle="true"><mn>4</mn><mi>t</mi></mstyle></math> .

Do you know how to Multiply (4t+4)/(t-5)*(t^2-t-20)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.